2019
DOI: 10.1038/s41598-019-47573-y
|View full text |Cite|
|
Sign up to set email alerts
|

Early Cellular Responses of Prostate Carcinoma Cells to Sepantronium Bromide (YM155) Involve Suppression of mTORC1 by AMPK

Abstract: The imidazolium compound YM155, first discovered as a potent inhibitor of Survivin, effectively kills many carcinomas in preclinical models. However, the upstream signaling mechanism triggered by YM155 remains unclear. Here we studied early signaling responses in vitro in prostate and renal cancer cell lines in a dose-dependent manner. We found that YM155 rapidly activates the retinoblastoma protein, correlating with the loss of expression of all three Cyclin Ds. Using Western blot, vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 72 publications
3
11
0
Order By: Relevance
“…Polysome profiles were generated in renal and prostate cancer cell lines following YM155 treatment which showed that YM155 substantially suppresses cap-dependent translation of mRNAs that include survivin [31]. Before any noticeable changes in mRNA transcripts, this experiment showed a significant suppression in translation as early as 4 hours after the start of YM155 treatment.…”
Section: Introductionmentioning
confidence: 94%
“…Polysome profiles were generated in renal and prostate cancer cell lines following YM155 treatment which showed that YM155 substantially suppresses cap-dependent translation of mRNAs that include survivin [31]. Before any noticeable changes in mRNA transcripts, this experiment showed a significant suppression in translation as early as 4 hours after the start of YM155 treatment.…”
Section: Introductionmentioning
confidence: 94%
“…Upon cellular stresses, AMPK interacts with and phosphorylates ULK1 on Ser 317 and Ser 777, leading to the dissociation of the ULK1-mTORC1 complex, translocation of ULK to the pre-autophagosomal membrane and eventually induction of autophagy [ 79 ]. Alternatively, AMPK may inhibit mTORC1 activation by directly phosphorylating raptor on two conserved serine residues (Ser722 and Ser792) [ 81 ]. Lately, several new findings have suggested that ULk1 provides potential negative feedback for AMPK activity by phosphorylating all three subunits of AMPK (AMPK-α, β and -γ) [ 25 , 82 ].…”
Section: Key Pathways Regulating Autophagy Activity In Admentioning
confidence: 99%
“…Sepantronium bromide (YM155) was introduced as an anti-cancer drug candidate that inhibits expression of the BIRC5 gene, which encodes the protein survivin [1]. In the meantime, YM155 has been suggested to exert additional and/or alternative mechanisms of anticancer actions, including induction of DNA damage, inhibition of NFκB signaling, induction of death receptor 5 expression, and/or suppression of MCL-1, XIAP, cIAP-1/2, BCL-2, BCL-XL, FLIP, EGFR, and/or mTORC [2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%